The Influence of Tax Exclusion Policies and Other Factors on the Value of Dividends Paid by Public Companies in Indonesia - Rizal, Mohamad Nor; Supriyadi; Fachrudin, Mohammad (Yayasan Ilomata, 2024)
This research aims to determine the effect of the dividend exclusion policy as a tax object as regulated in the Undang-Undang Cipta Kerja and its derivatives on dividends paid by companies. It is hoped that dividend payments can become a source of investment in Indonesia so that an increase in the amount of dividends paid will increase investment in Indonesia. This research also wants to know the effect of net profit, return on assets (ROA), free cash flow (FCF), and debt-to-equity ratio (DER) on the dividends paid by the company. The data used in the research is data from 2017 – 2022 which comes from 30 companies with the largest market capitalization on the IDX. The analysis was carried out using multiple linear regression on panel data using the Stata application version 16. Based on the research results, it is known that the policy of excluding dividends as a tax object does not have a significant effect on the dividends paid by companies. Meanwhile, net profit, ROA, and FCF have a significant and positive effect on the dividends paid by the company. DER is also known to have a significant and negative effect on the dividends paid by companies. The implication of this research is that to increase the dividends paid by the company, the policies implemented must be able to be utilized by the majority shareholders and there will be an increase in the company's net profit, ROA, and FCF as well as a decrease in DER.